al-Tawḥīd ʿinda Ismāʿīl Rājī al-Fārūqī wa-Ishhāmātuhu fī Taṭwīr ʿIlm al-Kalām al-Jadīd - Inayah, Firda; Khasanah, Neneng Uswatun (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This article discusses the concept of tawḥīd (the oneness of God) according to Ismail Raji al-Faruqi and his contribution to the development of the new Islamic theology. This study forms part of the foundational research in Islamic studies within the broader effort toward reform and renewal, aimed at strengthening the Islamic worldview in the face of globalization and modernity. The type of this study is qualitative research using a descriptive-analytical method. The findings of the study conclude that tawḥīd, for al-Faruqi, is not merely a doctrinal concept meaning the acknowledgment of the centrality of the Creator in worship but rather, it constitutes a comprehensive system of belief that defines a person’s overall worldview regarding existence and life. Accordingly, al-Faruqi believed that tawḥīd, that is, the testimony